Klippel-Trenaunay Syndrome Causing Life-Threatening GI Bleeding: A Case Report and Review of the Literature - Salih Samo; Muhammed Sherid; Husein Husein; Samian Sulaiman; Margaret Yungbluth; John A. Vainder (Case Reports in Gastrointestinal Medicine)
Klippel-Trenaunay syndrome (KTS) is a rare congenital syndrome of vascular malformations and soft tissue and bone hypertrophy. Vascular malformations can affect multiple organ systems. Involvement of the gastrointestinal (GI) tract is uncommon in KTS, but it can be a source of life-threatening bleeding. We report a case of a 32-year-old male with a known diagnosis of KTS who presented with a life-threatening rectal bleeding and was treated with proctosigmoidectomy and massive blood products transfusion. He expired after a long hospitalization. We then review the literature on KTS and management of some of its complications.